Differential characteristics and in vitro angiogenesis of bone marrow‐ and peripheral blood‐derived endothelial progenitor cells: evidence from avian species. (13th May 2014) - Shah, Q. A.; Tan, X.; Bi, S.; Liu, X.; Hu, S.
Abstract Objectives This study was conducted to compare phenotypes and in vitro angiogenic capacity of putative endothelial progenitor cells (EPCs) derived from bone marrow (BM) and peripheral blood (PB), from an avian species. Materials and methods Mononuclear cells were isolated from chicken BM and PB (BMMNCs and PBMNCs) and cultured in EGM‐2 medium. Cells at days 7–14 were used for the experiments. Expression of progenitor and endothelial markers, number of Dil–ac–LDL/lectin dual‐positive cells and adipogenic and osteogenic differentiation were determined. Migration and in vitro angiogenic ability between BMMNC‐ and PBMNC‐derived cells were compared. Results PBMNCs developed typical EPC appearance, with initial spindle shape followed by a cobblestone form, whereas BMMNC‐derived cells retained their constitutive spindle‐like morphology throughout the study. Cells derived from both sources expressed CD133, CD31 and VEGFR‐2, although PBMNCs‐derived cells had lower CD133 expression. Nevertheless, number of Dil–ac–LDL/lectin dual‐positive cells did not differ between groups. Adipogenic and osteogenic lineages were verified in BMMNC‐ but not in PBMNC‐derived cells. PBMNC‐derived cells formed tubular networks on Matrigel. However, BMMNC‐derived cells formed few tube‐like structures, which were not morphologically comparable to those developed by their counterparts. Conclusion Our results suggest that so called EPCs derived from BMMNCs are not 'true' EPCs, supporting previous findings on mammals that BM may not serve as an optimal isolation source of EPCs.